Cyclic microbridge testing of graphene oxide membrane. (May 2017) - Wu, Quan; Dai, Zhaohe; Su, Yanjing; Volinsky, Alex A.; Liu, Luqi; Zhong, Zhang
Abstract: Theoretical formula to determine flexible membrane deformation of microbridge test was derived based on the assumption that the membrane deformation is dominated by stretching, opposite to bending. Microbridge samples were fabricated from 0.17 μm thick free-standing graphene oxide membrane placed on patterned silicon substrates and tested with a nanoindentation system. The effective Young's modulus was determined from the microbridge test during both loading and unloading. Combining the flexible membrane theoretical formula with deformable tension-shear model, a multiscale model was proposed to determine the shear modulus of graphene oxide membrane. The effect of temperature on Young's modulus in different loading sequence was investigated. Polarized Raman spectroscopy and X-ray diffraction were utilized to characterize the self-stiffening behavior of graphene oxide membranes. Graphical abstract: